Kinetic and thermodynamic studies on the removal of Cu(II) ions from aqueous solutions by adsorption on modified sand - Gusain D.; Srivastava V.; Sharma Y.C. (My University, 2025)
Studies on the removal of copper by adsorption on modified sand have been investigated. The adsorbent was characterized by XRD, FTIR and SEM. Removal of Cu was carried out in batch mode. The values of thermodynamic parameters namely δG0, δH0 and δS0 at 25°C were found to be -0.230kcal-1mol-1, +4.73kcal-1mol-1 and +16.646calK-1mol-1, respectively. The process of removal was governed by pseudo second order rate equation and value of k2 was found to be 0.122gmg-1min-1 at 25°C. The resultant data can serve as baseline data for designing treatment plants at industrial scale. © 2013 The Korean Society of Industrial and Engineering Chemistry.